Do functional-performance tests detect impairment in subjects with ankle instability? - Munn, J; Beard, D; Refshauge, K; Lee, R (2002)
Objective: To determine whether the triple-crossover hop and timed shuttle run are able to discriminate between injured and uninjured limbs in subjects with functional ankle instability. Design and Setting: A comparative study involving the assessment of functional performance, conducted in a university gymnasium. Participants: A volunteer sample of 16 university-age subjects with unilateral functional ankle instability. Outcome Measures: The triple-crossover hop for distance and timed shuttle run measured functional performance, with the uninjured limb acting as a control. Subjects also rated their ankle symptoms using a self-report questionnaire. Results: The triple-crossover hop and shuttle run did not detect functional deficit despite subjects' self-report scores indicating functional impairment. Conclusions: Results of the triple-crossover hop and shuttle run used in the clinic should be interpreted with caution, because they will not necessarily identify functional impairment.